PEMBENTUKAN KARAKTER ANAK MELALUI SEKOLAH SEPAK BOLA DALAM PERSPEKTIF SOSIOLOGI OLAHRAGA - Sinaga, Betrandavid; Natanael Simanullang, Frengky; Nurkadri; Lamasi Siburian, Daniel; Marnasip Simbolon, Jobson (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Football schools are one of the sports coaching institutions that function not only to improve football playing skills but also to shape children's character. Through training activities, competitions, and social interactions within the team, children learn discipline, responsibility, teamwork, sportsmanship, and leadership. This study aims to analyze the process of character building in children through football schools from the perspective of sports sociology. The study used a qualitative method with a descriptive approach through literature studies from various journals, books, and scientific articles. The results show that the football school environment has a significant influence on children’s social and moral development through the role of coaches, interactions among players, and family support. In addition to providing positive impacts, character building in football also faces challenges such as achievement pressure, sports fanaticism, and social media influence. Therefore, balanced sports coaching between achievement and character education is needed so children can develop into quality individuals.